Religious life of the Japanese people - Anesaki, Masaharu (Kokusai Bunka Shinkokai, 1961)
The book was well-receiced by the english speaking world, and was soon out of print, to the disappointment of many who were interested in its subject matter. This contens includes: general observations, shinto, the indigenous religion; Chinese culture: confucianism and Taoism,...